Daur Ulang Air Leri Dalam Mengurangi Limbah Rumah Tangga - Aminudin; Widi Hastomo; Fiedha Nasution (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
This community service aims to educate the community in Bambu Apus Pamulang to be more concerned about waste. Households are productive producers of waste, household waste water can be used as liquid organic fertilizer for hydroponic plants, the water content of leri is nitrogen, phosphorus, potassium, calcium, magnesium, sulfur, iron, and vitamin B1. Hydroponics is considered suitable for urban communities, because it does not require a large place, is relatively safe from insects and the harvest period can be controlled, the results are expected to be able to meet the nutritional needs of households with organic vegetables. These community service activities are carried out so that the community is aware of the importance of protecting the environment, starting with simple matters, providing information that households are able to process and utilize leri's waste water, and finally teaching the community members how to grow hydroponic vegetables to ensure the nutrition of families with organic vegetables independently.